Diet-related knowledge, attitudes, and behaviors among young and middle-aged individuals with high-normal blood pressure: A cross-sectional study in China - Mu, Tingyu; Xu, Rixiang; Zhu, Qianyin; Chen, Lingshan; Dong, Die; Xu, Jiayi; Shen, Cuizhen (Frontiers in Public Health, 2022)
Background Dietary modifications play an important role in the prevention and management of high-normal blood pressure (BP). The aim of this study was to investigate diet-related knowledge, attitudes, and behaviors, and the socio-demographic determinants of these, among young and middle-aged Chinese individuals with high-normal BP. Methods Data from the 2015 China Health and Nutrition Survey (CHNS) were analyzed in this study. A total of 1,756 subjects with high-normal BP were included. A chi-square test and binary logistic regression analysis were conducted to identify the risk factors toward diet-related knowledge, attitudes, and behaviors. Results A total of 37.4% of the participants knew about the Chinese Food Pagoda (CFP) or the Dietary Guidelines for Chinese Residents (DGCR). Overall, 39.8% of the subjects were classified as having adequate diet-related knowledge literacy, 27.8% reported positive diet-related attitudes to healthy eating, and 35.3% reportedly looked for nutrition knowledge. Of note, 72.4% and 80.1% of the participants reported liking to eat fruits and vegetables, respectively. Individuals with a middle school education [odds ratio (OR) = 1.784, 95% CI = 1.236–2.576], high school/vocational education (OR = 1.944, 95% CI = 1.305–2.896), and college degree or above (OR = 2.089, 95% CI = 1.341–3.322), who were living in a rural area (OR = 1.311, 95% CI = 1.048–1.639), proactively looking for nutrition knowledge (OR = 1.529, 95% CI = 1.227–1.906), and reported liking to eat vegetables (OR = 1.939, 95% CI = 1.409–2.688), were more likely to have sufficient dietary knowledge literacy. Managers (OR = 1.655, 95% CI = 1.039–2.635) were more likely to have positive dietary attitudes. Female gender (OR = 1.396, 95% CI = 1.089–1.790), high school/vocational school education (OR = 2.071, 95% CI = 1.269–3.379), college degree and above (OR = 2.207, 95% CI = 1.262–3.862), knowledge about the CFP or DGCR (OR = 8.138, 95% CI = 6.326–10.468), and sufficient dietary knowledge literacy (OR = 1.338, 95% CI = 1.050–1.705) were associated with an increased likelihood of looking for nutrition knowledge. Conclusion Individuals with high-normal BP, predominantly males, living in rural area, with lower education, farmers, workers, service workers, and workers in the non-government employment unit may have poor diet-related knowledge, attitudes, and behaviors.